Analisis Normatif tentang Hakim sebagai Penentu Keabsahan Objek Hukum dalam Perjanjian - Atentri Melza; Cece Pramana; Gustiya Sunarti (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
This research aims to comprehensively examine several important elements in Islamic law, namely the meaning of judge, legal object, legal subject,mukallaf, the concepts of Ahliyyatul wujûb and Ahliyyatul adâ', as well as the conditions attached to legal objects and legal subjects. This study starts from the understanding that law is not just a formal rule, but a system of norms that regulate human relationships with God, with fellow humans, and with their environment. In this context, judges have a central position as parties who are given the authority to uphold justice through legal decisions. The object of law is understood as everything that can be the target of rights and obligations, while the subject of law is the parties who have rights and obligations, namely humans asmukallaf. The concept ofmukallaf is closely related to Ahliyyatul wujûb, namely a person's eligibility to receive rights from the womb, and Ahliyyatul adâ', namely the eligibility to carry out obligations perfectly after reaching puberty. Furthermore, this research also examines the conditions that must be met for legal objects and subjects to be legally valid. The results of this study are expected to provide a systematic understanding of the basic structure of Islamic law, so that it can become a theoretical and practical basis for the development of legal science and its application in society.